TA’ADDUD AL-WUKALÂ‘: KONSEP MULTIPLE AGENTS DALAM FIKIH MUAMALAH - Mulyono Jamal; Nurul Fathonah (Muslim Heritage, 2022)
AbstractThis study aims to determine the concept of multi-representation in wakalah fiqh muamalah perspective and the law of delegating representatives by representatives to other people so that they become multi-layered representatives for their muwakkil or parties who give power to representatives. This takes a case study on land brokers who often look for other agents or brokers to help with their work, whether the muwakkil knows or not. This research is a qualitative descriptive using a literature approach. The result of the research is that it is allowed for a representative to find another representative even without the permission of the muwakkil on the condition that it does not violate the rules of the Shari'a, endangers the benefit of the muwakkil and aims to help the agent's work. AbstrakPenelitian ini bertujuan untuk mengetahui konsep multiwakil dalam wakalah perspektif fikih muamalah serta hukum melimpahkan perwakilan oleh wakil kepada orang lain sehingga menjadi wakil berlapis bagi muwakkil-nya atau pihak yang memberikan kuasa kepada wakil. Hal ini mengambil studi kasus pada makelar tanah yang sering mencari agen atau broker lain untuk membantu pekerjaannya baik sepengetahuan muwakkil atau tidak. Penelitian ini adalah deskriptif kualitatif dengan menggunakan pendekatan pustaka.Hasil dari penelitian adalah dibolehkan seorang wakil untuk mencari wakil lainnya meski tanpa ijin muwakkil dengan syarat tidak melanggar aturan syariat, membahayakan maslahat muwakkil dan bertujuan untuk membantu pekerjaan wakil.